Edaphic ascid mites (Acari: Mesostigmata: Ascidae) from the state of São Paulo, Brazil, with description of five new species - de C. Mineiro, Jeferson L.; Lindquist, Evert E.; de Moraes, Gilberto J. (Zootaxa, 2009)
This paper reports the occurrence of 11 species of edaphic mites of the family Ascidae collected from soil and litter in southeastern Brazil. Five are new to science, namely Cheiroseius neophalangioides sp. nov., Gamasellodes magniventris sp. nov., Lasioseius latinoamericanus sp. nov., Proctolaelaps paulista sp. nov. and Protogamasellus sigillophorus sp. nov.. Among the other species collected, diagnoses and collection data are provided for Asca garmani Hurlbutt, 1963, Blattisocius tarsalis (Berlese, 1918), Proctolaelaps diffissus Karg, 1976 and Protogamasellus mica (Athias-Henriot, 1961 ); these are the first Brazilian collection records for these species other than B. tarsalis in stored products. Lasioseius helvetius Chant, 1958 is considered a senior synonym of L. saltatus Karg, 1980 (new synonymy), the latter reported previously from Brazil. Lasioseius quinisetosus Lindquist & Karg, 2006 (= Cheiroseius inguinalis Karg, 1977) is newly recorded from Brazil. Diagnoses and redescriptions are provided for L. helvetius and L. quinisetosus. Proctolaelaps intermedius Athias-Henriot, 1959 is considered a senior synonym of P. orientalis (Chant, 1963) and P. wenkochingi “(Samšinák, 1964)” (new synonymies).